Address as a Condition for Ratifying the Advertisements in Armenian Periodicals of Tiflis (1846-1918) - DANIELYAN, TARON (Bulletin of Yerevan University B: Philology, 2021)
Address as a condition for ratifying the advertising messages in Armenian Periodicals of Tiflis had some peculiarities in its development that was conditioned by legislative, administrative, and economic reforms, as well as, was the result of improvements in communication channels and means. According to data integrity addresses are combinations of independent information units each of which has a different meaning and correlatives and in combination with other units creates new information unit the integrity of which is conditioned by the level of comprehension by which the message recipients get the new information unit.